DIAGNOSTIC EFFICACY OF STOOL ANTIGEN TEST (HPSA), CLO TEST AND SEROLOGY FOR THE DETECTION OF HELICOBACTER PYLORI INFECTION - Baqai, R.; Qureshi, H.; Arian, G.,; Mehdi, I. (Journal of Ayub Medical College Abbottabad, 2003)
Background: The diagnosis of Helicobacter pylori infection was initially being made through invasive methods but now non invasive methods have been developed to make the diagnosis easier. The present study was done to evaluate the diagnostic efficacy of a two non invasive tests i.e. Helicobacter pylori Stool antigen test (HpSA) and Helicobacter pylori IgG serology with an invasive method i.e. Campylobacter like organism (CLO) gel test. Methods. The study was conducted in the gastroenterology unit of Pakistan Medical Research Council Research Centre Karachi. Adult patients with gastroduodenal disease were selected for study and their medical history was recorded. Endoscopy was done on all patients and the antral biopsy sample was tested for H.pylori using CLO test. Serology (IgG) was done elsewhere using ELISA and titers of over 50 units were recorded as positive. HpSA was done to determine the presence of H.pylori antigen in stool. Results. Out of 43 patients 34 (79%) were males and 9 (21%) females. The main presenting symptom was epigastric pain in 74 % cases. Although H.pylori IgG antibody titers of over 50 were taken as positive but for this study titres of over 100 were taken as significant for comparison with other tests . CLO test was positive in 26 (60.5%) cases, H. Pylori antibody titers of over 100 IU were present in 33 (76.7%) cases and HpSA in 21 (48.8 %). Using CLO test as the gold standard the sensitivity of serology was 81 % and that of HpSA 65% with a 29% and 76 % specificity respectively. Conclusion. In our setting CLO test is still the best diagnostic test for H. Pylori detection. Both non invasive tests i.e. serology and stool HpSA are less sensitive than CLO but amongst each other both are equally sensitive. Keywords: Helicobacter Pylori, Stool Antigen Test, Serology